PRACTICAL SOCIALIZATION OF THE USE OF CANVA MAGIC AI AS A SOLUTION FOR DIGITAL LEARNING MEDIA DEVELOPMENT FOR TEACHERS AT STATE PRIMARY SCHOOL 091333 RAYAUSANG DOLOK MASAGAL DISTRICT, SIMALUNGUN DISTRICT MASAGAL KABUPATEN SIMALUNGUN - Munthe, Melda Veby Ristella; Sibarani, Imelda Sabrina; Sihite, Rotua Agustina; Clara, Elisabet Dwi; Silalahi, Ariel Onivedi (Universitas Negeri Medan, 2024)
Current technological developments in the world of education are very significant because the world of education must be able to adapt to technological changes in order to improve the quality of education. Global demands also require the world of education to always adapt to technological developments to improve the quality of education (Reka et al, 2022). The quality of education really depends on the quality of the teacher and his learning methods. Learning media can be interpreted as a tool in the teaching and learning process. Apart from that, learning media also includes everything that is used to stimulate thoughts, feelings, attention, and abilities or skills, so that it can encourage the learning process. One digital learning media that can improve the quality of learning is the use of Canva Magic Al. Canva Magic Al is a graphic design platform that allows users to create graphics, presentations, posters, logos, documents and other social media visual content. This platform is available on web and mobile, and integrates millions of images, fonts, templates, and illustrations. In this community service activity, the Canva Magic Al application was chosen as a tool that will be used by teachers to create attractive presentation designs for teaching materials. Canva Magic Al is an application that is popular in the world of technology to make teaching materials that are more creative and can also be used as teaching media.